Entropy-Mediated Lattice Distortion for Tailored Dielectric Polarization to Improve L-Band Electromagnetic Wave Absorption - Ding, Han; Li, Yibo; Wang, Yu; Song, Weikang; Wang, Xuan; Han, Xijiang; Xu, Ping; Du, Yunchen (Nano-Micro Letters, 2026)
Due to the long wavelength of L-band, the precise regulation of electromagnetic (EM) parameters to achieve efficient EM absorption in this frequency range remains a formidable challenge. Here, low-entropy, medium-entropy, and high-entropy (HEA) alloys are designed via a configurational-entropy control strategy, which progressively enhances lattice distortion and reconstructs the electronic structure, thereby enabling precise tuning of real (εr′) and imaginary parts (εr″) of the complex permittivity under robust EM loss. Experiments and density functional theory demonstrate that increasing configurational entropy intensifies lattice distortion in multi-principal element alloys, disrupts local central symmetry within the crystal structure, induces an asymmetric reconstruction of the electron cloud, and breaks the degeneracy of electronic states. This process establishes massive dipole polarization centers at the atomic scale. Furthermore, the rugged potential energy surface constructed by this severe distortion imposes a higher energy barrier against the dynamic orientational relaxation of dipoles, which prolongs polarization relaxation time and effectively amplifies the low-frequency dielectric polarization loss. Benefiting from this entropy-driven lattice-distortion effect, the HEA achieves a minimum reflection loss of − 22.7 dB at 1.7 GHz (99.46% absorption efficiency) and an L-band coverage of 80.5% (RL ≤ − 5 dB). 3D gradient multilayer metamaterial structure broadens the bandwidth, achieving absorption of almost 0.5 to 8 GHz (RL ≤ − 10 dB) at 8 mm thickness. Additionally, HEA shows excellent radar stealth and corrosion resistance. This work elucidates the mechanism through which entropy-driven lattice distortion modulates the EM response, providing a novel research paradigm for designing low-frequency EM functional materials via micro-lattice engineering. Highlights: 1 This work employs a configurational-entropy control strategy to progressively enhance lattice distortion in multi-principal element alloys, thereby reconstructing their electronic structure and balancing electromagnetic parameters under high electromagnetic loss. 2 Density functional theory calculations demonstrate that entropy-induced lattice distortion further drives asymmetric electron cloud reconstruction, thus forming numerous dipolar polarization centers, which enhances low-frequency dielectric attenuation of high-entropy alloy (HEA). 3 HEA exhibits excellent low-frequency electromagnetic absorption, radar stealth, and corrosion resistance, while metamaterial structural design further broadens its absorption bandwidth.